Measuring practice effort
This fifth issue of Coaching Science Abstracts reviews articles concerned with measuring training effectiveness. There is a strong trend today to assess the impact of training. Three common indexes, lactate accumulations, heart rates, and perceived exertion, are generally used without question. For sports that are aerobically oriented, anaerobic threshold is used as the criterion for training benefits. However, these measures may not be as valid or reliable as is often assumed. The main question that should be asked by a coach or athlete when requested to complete a measurement or test is, how relevant is it for measuring what occurs in the sport? A discussion about the utility of a measure could continue ad infinitum. The principal concern of any coach or athlete should be that if something is measured, what extra information does it add to the perceptions of the coach and athlete so that better coaching decisions can be made. Testing for testing-sake, does not serve a worthwhile purpose. Unless a measurement about an aspect of an athlete's performance can be related to the total performance, it may not be very useful. In the complexity that is an athlete, a single factor has to be considered in light of its interaction with the myriad of other factors that govern performance. If that is not done, then the considerations used to make coaching decisions may not be sound because they would be too limited. Measuring practice effort is intended to provide glimpses of what is said about frequently used measures of the training response. The articles contained are: LACTATE 1. LACTIC ACID Rushall, B. S. (1967). The scientific bases of circulorespiratory training. Unpublished master's thesis, Indiana University, Bloomington, Indiana. 2. LACTATES Jacobs, I. (1983). Blood lactate and the evaluation of endurance fitness. SPORTS, W-2, 6 pp. 3. LACTATE TESTING AND USES IN SWIMMING Troup, J. P. (Ed.). (1990). Selection of effective training categories. In International Center for Aquatic Research annual: Studies by the International Center for Aquatic Research 1989-90. Colorado Springs, CO: United States Swimming Press. 4. VALUE OF LACTATES IN ROWING Roth, W. (1991). Physiological-biomechanical aspects of the load development and force implementation in rowing. FISA Coach, 2(4), 1-9. 5. LACTATE MEASUREMENT RELIABILITY Nishibata, I., Sakata, N., Ogawa, S., & Okumura, M. (1993). Better reproducibility of 2 and 4 mM blood lactate threshold than Inflection points. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 363. 6. LACTATES AND ENDURANCE PERFORMANCE Rusko, H. (1986). Analysis of physiological response to training and competition among Finnish endurance athletes. Athletic Performance Review, 1(10), 1-2 (Abstract). 7. LACTATES AND COMPETITIVE PERFORMANCES Bonifazi, M., Martelli, G., Marugo, L., Sardella, F., & Carli, G. (1993). Blood lactate accumulation in top level swimmers following competition. The Journal of Sports Medicine and Physical Fitness, 33, 13-18. 8. USING LACTATES IN THE REAL WORLD Rushall Thoughts, 1993. 9. CAUTIONS ABOUT THE USE OF BLOOD LACTATES Anderson, G. S., & Rhodes, E. C. (1991). Relationship between blood lactate and excess CO2 in elite cyclists. Journal of Sports Sciences, 9, 173-181. 10. FURTHER SKEPTICISM ABOUT LACTATES Koutedakis, Y. (1995). Seasonal variation in fitness parameters in competitive athletes. Sports Medicine, 19, 373-392. 11. THE LACTATE DEBATE Rushall, B. S. (1991). The lactate debate - one more time. Journal of the Australian Swim Coaches' Association, 8(3), 8-12. 12. AN ENERGY METABOLISM DIFFERENCE IN WOMEN Esbjornsson, M., Bodin, K., & Jansson, E. (1995). Muscle metabolism during a 30-s sprint test (Wingate Test) in females and males. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 448. HEART RATE 13. RELATIONSHIP BETWEEN HEART RATE AND LACTIC ACID Howat, R. C., & Robson, M. W. (June, 1992). Heartache or heartbreak. The Swimming Times, 35-37. 14. HEART RATE AND LACTATE CONCENTRATIONS IN CROSS COUNTRY SKIERS Gibbons, T. P., & Watts, P. B. (1993). Heart rate and blood lactate concentration during on-snow training in college cross country skiers. Medicine and Science in Sports and Exercise, 25(5), Abstract 734. 15. HEART RATE NOT A GOOD VO2MAX INDICATOR Emmett, J. D., & McClung, J. A. (1993). Heart rate as an indicator of oxygen uptake & cardiac function during two swimming modes. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 634. 16. HEART RATE VARIATION AND PERFORMANCE PARAMETERS Richardson, R. S., Verestraete, D., Hochstein, A., Schultz, W., Johnson, S. C., Luetkemeser, M. J., & Stray-Gundersen, J. (1993). The role of hypervolemic and stroke volume in the heart rate and oxygen relationship following intense training. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 582. 17. HEART RATES AND BREATHING Srouffe, L. A. (1971). Effects of depth and rate of breathing on heart rate and heart rate variability. Psychophysiology, 8, 648-655. 18. HEART RATE VARIABILITY Sayers, B. McA. (1973). Analysis of heart rate variability. Ergonomics, 16, 17-32. 19. HEART RATE REDUCTIONS Author unknown. 20. PROBLEMS WITH HEART RATES AND SWIMMING Ueda, T., & Kurokawa, T. (1995). Relationships between perceived exertion and physiological variables during swimming. International Journal of Sports Medicine, 16, 385-389. 21. RUNNING AND SWIMMING HEART RATES DiCarlo, L. J., Sparling, P. B., Millard-Stafford, M. L., & Rupp, J. C. (1991). Peak heart rates during maximal running and swimming: implications for exercise prescription. International Journal of Sports Medicine, 12, 309-312. 22. HEART RATE AND MENTAL-PHYSICAL ACTIVITY Desharnais, R., Jobin, J. & Desgagnes, P. (1995). Interaction of physical and mental stresses on heart rate and effort sense during exercise. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 355. 23. HEART RATES, RPE, AND 5 km RUNNING Evans, B. W., & Potteiger, J. A. (1995). Using heart rate and ratings of perceived exertion to monitor intensity during a 5 km run in trained runners. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 906. RATINGS OF PERCEIVED EXERTION 24. BORG'S RPE - ITS VALUE FOR SPORTS TESTING Borg, G. (1985). An introduction to Borg's RPE-scale. Ithaca, NY: Mouvement Publications. 25. RPE INDICATES WORK LOAD Steed, J. C., Gaesser, G. A., & Wellman, A. (1993). Ratings of perceived exertion (RPE) as markers of blood lactate concentration during running. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 367. 26. RPE BETTER INDICATOR OF WORK THAN HEART RATE Roach, B. P., Croisant, P. T., & Emmett, J. D. (1993). The appropriateness of heart rate and RPE as measures of intensity during three variations of aerobic dance. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 113. 27. RPE NOT A GOOD INDEX Potteiger, J. A., & Weber, S. F. (1994). Rating of perceived exertion and heart rate as indicators of exercise intensity in different environmental temperatures. Medicine and Science in Sports and Exercise, 26(6), 791-796. 28. RPE A GOOD TOOL FOR PRESCRIBING EXERCISE INTENSITY Steed, J., Gaesser, G. A., & Weltman, A. (1994). Rating of perceived exertion and blood lactate concentration during submaximal running. Medicine and Science in Sports and Exercise, 26(6), 797-803. 29. RPE AND PHYSIOLOGY IN SWIMMING Ueda, T., & Kurokawa, T. (1995). Relationships between perceived exertion and physiological variables during swimming. International Journal of Sports Medicine, 16, 385-389. 30. RPE MEASURES WORK INTENSITY ACROSS EXERCISE MODES Ziogas, G., Thomas, T. R., Smith, T. D., Zhang, Q., & Londeree, B. R. (1994). Comparison of RPE at ventilatory and at 60% of VO2max on six different exercise modes. Medicine and Science in Sports and Exercise, 26(5), Supplement abstract 10. 31. RPE DOES NOT PREDICT AEROBIC DANCE PHYSIOLOGICAL RESPONSES Schaeffer, S. A., Browder, K. D., & Darby, L. (1994). Ratings of perceived exertion (RPE) and metabolic responses of females during aerobic dance exercise. Medicine and Science in Sports and Exercise, 26(5), Supplement abstract 869. 32. RPE IS RELATED TO MANY PHYSIOLOGICAL VARIABLES Womack, C. J., Davis, S. A., Blumer, J., Barrett, E., Gaesser, G. A., & Weltman, A. (1994). Effects of training and epinephrine infusion on mediators of ratings of perceived exertion. Medicine and Science in Sports and Exercise, 26(5), Supplement abstract 637. ANAEROBIC THRESHOLD 33. A COMPARISON OF METHODS OF MEASURING ANAEROBIC THRESHOLD IN SWIMMERS Harrison, J. R., Dawson, B. T., Lawrence, S., & Blanksby, B. A. (1992). Non-invasive and invasive determinations of the individual anaerobic threshold in competitive swimmers. Journal of Swimming Research, 8, 11-17. 34. LACTATE THRESHOLD, VO2max, AND ENDURANCE PERFORMANCE Hagberg, J. M. (1984). Physiological implications of the lactate threshold. International Journal of Sports Medicine, 5, 106-109. 35. ANAEROBIC THRESHOLD (LACTIC ACID TURNPOINT) Gibbons, E. S. (1987). The significance of anaerobic threshold in exercise prescription. Journal of Sports Medicine, 27, 357-361. 36. ANAEROBIC THRESHOLD TRAINING AND VO2max Rusko, H. (1987). The effect of training on aerobic power characteristics of young cross-country skiers. Journal of Sports Sciences, 5, 273-286. 37. FURTHER ON ANAEROBIC THRESHOLD Rushall Thoughts, 1988. 38. CRITICAL VELOCITY FOR MLSS Wakayoshi, K., Yoshida, T., & Moritani, T. (1993). Does critical swimming velocity represent exercise intensity at maximal lactate steady state? Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 366. SUGGESTED READING 39. TESTS OF THE PHYSICAL CONDITION OF ELITE SWIMMERS Rushall, B. S. (1995). Tests of the physical condition of elite swimmers: A manual for coaches.Sports Science Associates, 4225 Orchard Drive, Spring Valley, CA 91977.